Long-Lived Charge Carrier Photogeneration in a Cooperative Supramolecular Double-Cable Polymer - Joseph, Jan; Berrocal, José Augusto; Casellas, Nicolás M.; Guldi, Dirk Michael; Torres, Tomás; García-Iglesias, Miguel (Journal of the American Chemical Society, 2024)
A newly designed C3-symmetric disc-shaped chromophore, BTT(NDI)3, features electron accepting naphthalene diimides linked to an electron donor BTT core. BTT(NDI)3 self-assembles in apolar solvents into highly ordered, chiral supramolecular fibers through π-π and 3-fold hydrogen-bonding interactions. This leads to a cooperative formation of plane-to-plane stacking of BTTs and J-aggregation of the outer NDIs. Such a structure ensures high charge mobility. Only photoexcitation of BTT in the BTT(NDI)3 polymers triggers a unidirectional electron transfer from BTT to NDI and results in (BTT•+-NDI•-) lifetimes that are by up to 3 orders of magnitude longer compared to (NDI•+-NDI•-) that is formed upon NDI photoexcitation. A multiphasic decay implies ambipolar pathways for charge carriers, that is, electron and hole delocalization along the respective BTT and NDI stacks. Our supramolecular approach offers potential for developing functional supramolecular polymers with continuous pathways for electrons and holes and, in turn, minimizing charge recombination losses in organic photovoltaic devices.
CRIS-Team Scopus Importer:2024-11-01